Adherence to United European Gastroenterology Guidelines on Diagnosis and Therapy of Immunoglobulin-G4-Related Digestive Disease - Vujasinovic, Miroslav; Lanzillotta, Marco; Culver, Emma L.; Rebours, Vinciane; Drenth, Joost P. H.; Stojkovic Lalosevic, Milica; Vikse, Jens; Gubergrits, Natalya; Hirth, Michael; Cardinale, Vincenzo; Motta, Rodrigo Vieira; Della-Torre, Emanuel; et al. (United european gastroenterology journal, 2025)
Introduction United European Gastroenterology (UEG) Guidelines on immunoglobulin G4 (IgG4)-related digestive disease provides evidence-based recommendations for the diagnosis and management of IgG4-related digestive disease. The aim of this study is to evaluate the adherence to recommendations of this IgG4 guideline across centers in Europe. Patients and methods Questionnaire-based data related to organ involvement, diagnosis, treatment and follow-up of newly diagnosed patients with IgG4-related digestive diseases over a 3-year period, were collected from 14 centers in 11 European countries. Results One hundred and ninety-nine patients (76% males) were included. Median age at diagnosis was 64 years. Most of the patients had concomitant pancreatic and biliary tree involvement (46%), followed by isolated pancreatic involvement (33.5%), isolated biliary tree involvement (18.5%), esophageal involvement (1.5%) or bowel (0.5%) involvement. Most of the patients (64%) underwent a combination of computed tomography and magnetic resonance imaging at diagnosis. Among the 158 autoimmune pancreatitis patients with or without concomitant bile duct involvement, treatment was performed according to guidelines in 115 patients (73%; moderate adherence). Follow-up assessment was performed between 2 and 4 weeks in 75 patients (47%, partial adherence). Among 37 patients with liver- or biliary tree involvement, 29 patients were treated according to guidelines (78%; full adherence). In the follow-up of patients with isolated liver- or biliary tree involvement, we observed moderate adherence in 21 (57%). Disease monitoring for activity and damage using the IgG4 responder activity index was utilized in only 3/14 centers (poor adherence). Conclusions IgG4-related digestive disease is restricted to the pancreas and bile ducts in the majority of patients. Even in specialist centers with an interest in IgG4-related digestive disease, UEG guideline treatment adherence was moderate, follow-up at 2-4 weeks was only partial, and monitoring for disease activity was poor. These findings highlight the need for ongoing education and improved adherence to monitoring among healthcare providers.
Zuerst veröffentlicht: 22. Juli 2025
Gesehen am 22.09.2025